Efektifitas Penggunaan Metode Bernyanyi Lagu “Tebak Aku” dalam Pengenalan Huruf Vokal Pada Anak Usia Dini - Nina Nuriyah Ma'arif; Rizka Kurniawati (Atthiflah: Journal of Early Childhood Islamic Education, 2022)
This article discusses the effectiveness of using the method of singing the song “Tebak Aku” in improving students' understanding about vowels letter for early child aged 3-4 years in KBIP Al-Muchlisin Gresik. This study uses a quantitative research experiment, namely one group pre-test and post-test design. In order to test the hypothesis whether or not there is a significant increase in the ability to recognize vowels before and after using the method singing the song “Tebak Aku”, this research utilises t-test for analysing the data. The findings have revealed that there is a significant increase in children's ability with regard to recognise vowels before and after using the method of singing the song "Tebak Aku". It can be seen from the result of the pre-test and post-test which has denoted that the score of Asymp.Sig (2-tailed) is 0.002 smaller than 0.05 as well as the result of the observational analysis that the average pre-test score is 51.26, while the average post-test score is 84.39. In addition, this teaching method is also able to motivate children aged 3-4 years to be decipline, active, responsive as well as able to to attract their interest in learning vowels letters.